Team planning discussion and clinical performance: a prospective, randomised, controlled simulation trial1. (15th February 2019) - Evain, J.‐N.; Perrot, A.; Vincent, A.; Cejka, J.‐C.; Bauer, C.; Duclos, A.; Rimmelé, T.; Lehot, J.‐J.; Lilot, M.
Summary: Planning held before emergency management of a critical situation might be an invaluable asset for optimising team preparation. The purpose of this study was to investigate whether a brief planning discussion improved team performance in a simulated critical care situation. Forty‐four pairs of trainees in anaesthesia and intensive care were randomly allocated to either an intervention or control group before participating in a standardised simulated scenario. Twelve different scenarios were utilised. Groups were stratified by postgraduate year and simulated scenario, and a facilitator was embedded in the scenario. In the intervention group, the pairs had an oral briefing followed by a 4‐min planning discussion before starting the simulation. The primary end‐point was clinical performance, as rated by two independent blinded assessors on a score of 0–100 using video records and pre‐established scenario‐specific checklists. Crisis resource management and stress response (cognitive appraisal ratio) were also assessed. Two pairs were excluded for technical reasons. Clinical performance scores were higher in the intervention group; mean (SD) 51 (9) points vs. 46 (9) in the control group, p = 0.039. The planning discussion was also associated with higher crisis resource management scores and lower cognitive appraisal ratios, reflecting a positive response. A 4‐min planning discussion before a simulated critical care situation improved clinical team performance and cognitive appraisal ratios. Team planning should be integrated into medical education and clinical practice.